Breeding Success and Mortality Rates in the Spot-billed Pelican (Pelecanus philippensis), at Telineelapuram Bird Protected Area, (An Iba Site; in 229) Srikakulam District, Andhra Pradesh, India - Ramamohan, H.; Kameswara Rao, K. (Indian Forester, 2017)
Breeding success and mortality rates of migratory birds are mainly depends on the available food resources, safe nesting sites and mortality of chicks. Present study revealed the breeding success and chick mortality in Spot-Billed Pelicans (Pelecanus philippensis), over a period of five years from 2008-2013, undertaken at a pelicanery of village Telineelapuram. The Spot-Billed Pelican (Pelecanus philippensis) is one of the important migratory birds visiting regularly for last 20 years. Overall breeding success during study period is considerable; however year wise statistics are differing. The recruitment percentage had ranged from a low of 24.44% in the year 2010 to a maximum of 47.11% in the year 2012 with an average success rate during five years study is 39.34%. At the same time, the rate of chick mortality was also high at Telineelapuram, due to the influence of different factors (namely Cyclones, Perching activity, Predations and Falling of chicks). The number of dead young birds during different years of the study period had ranged from 33 to 82. Highest mortality (82 individuals) was observed during the year 2010. The average mortality rate of chicks at Telineelapuram is 18.72% and detailed results were projected.